Expression of ADP receptor P2Y12, thromboxane A2 receptor and C-type lectin-like receptor 2 in cord blood-derived megakaryopoiesis. (4th July 2021) - Gerhards, Catharina; Uhlig, Stefanie; Etemad, Mani; Christodoulou, Foteini; Bieback, Karen; Klüter, Harald; Bugert, Peter
Abstract: The ADP receptor P2Y12, the thromboxane A2 receptor (TXA2 R) and the C-type lectin-like receptor 2 (CLEC-2) mediate platelet activation by different mechanisms. Only little is known about the expression of the receptors in human megakaryopoiesis. Our study aimed to establish a flow cytometry (FC) method for the measurement of P2Y12, TXA2 R, and CLEC-2 on platelets of healthy donors and to monitor receptor expression in ex vivo megakaryopoiesis. We determined mean fluorescence intensity (MFI) values of FITC, PE, or APC labeled antibodies binding to the receptors on platelets of 90 healthy donors. For cord blood-derived megakaryopoiesis (CBMK) differentiation of CD34+ cells was induced by IL-3, SCF, and TPO. At 6 time points between day 0 and day 21 of cell culture the MFI values for CD34, CD41, CD61, P2Y12, TXA2 R, and CLEC-2 were measured. Quantitative PCR was used for relative quantification of the corresponding mRNA. Transcription factor (TF) binding sites were predicted by in silico analysis of the genes. Platelets showed expectable high MFI values for the platelet marker CD41 (13, 716 median MFI). Lower MFI was found for P2Y12 (2, 847 median MFI) and CLEC-2 (1, 211 median MFI), whereas, binding of the TXA2 R antibody revealed even higher values (21, 458 median MFI) than CD41. In CBMK the CD34+ cells were negative for P2Y12, TXA2 R, and CLEC-2 at day 0. A maximum of 21-fold and 6-fold increase of P2Y12 and TXA2 R MFI values, respectively, was found on day 14 to 17. MFI for CLEC-2 increased by 58-fold within the first week and reached a maximum of 1, 572-fold increase within the first two weeks of CBMK. Very similar results were obtained on the RNA level. The differential regulation of receptor expression in CBMK was further supported by significant differences in the numbers and types of TF binding sites. P2Y12 and TXA2 R, both upregulated only to a low extent in CBMK, probably, are dispensable for megakaryopoiesis. Furthermore, we speculate that CLEC-2 strongly upregulated in early CMBK is important for megakaryopoiesis.